Understanding Hemifacial spasm: A Review Of An Uncommon Movement Disorder (Bangladesh Journal of Neuroscience, 2019)
Hemifacial Spasm is a rare condition and often misdiagnosed even by neurologists. Although etiology, pathophysiology is clear, treatment is unsuccessful in many cases. In this review article we focus on etiology, pathophysiology, diagnosis and management of this infrequent movement disorder.Bangladesh Journal of Neuroscience 2019; Vol. 35 (2): 104-109